2016
DOI: 10.1186/s12944-016-0247-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism rs5498 of the ICAM-1 gene affects the progression of carotid atherosclerosis in patients with type 2 diabetes mellitus

Abstract: BackgroundAdhesion molecules are involved in the development of atherosclerosis. An increased level of the ICAM 1 molecule is associated with numerous inflammatory diseases including atherosclerosis of carotid arteries. The rs5498 (K469E) polymorphism of the ICAM-1 gene leads to an increase in the level of serum ICAM. We investigated the association between the rs5498 (K469E) polymorphism of the ICAM-1 gene and the progression of carotid atherosclerosis in subjects with type 2 diabetes mellitus (T2DM). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Similarly, Gaetani et al showed that the presence of the EE genotype significantly independently increased the risk of PAOD (Gaetani et al, 2002). Popović et al in their study found that the EE genotype of the K469E polymorphism of the ICAM-1 gene was associated with a more rapid progression of carotid atherosclerosis in patients with type 2 diabetes mellitus than other genotypes (Gaspar et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Gaetani et al showed that the presence of the EE genotype significantly independently increased the risk of PAOD (Gaetani et al, 2002). Popović et al in their study found that the EE genotype of the K469E polymorphism of the ICAM-1 gene was associated with a more rapid progression of carotid atherosclerosis in patients with type 2 diabetes mellitus than other genotypes (Gaspar et al, 2016).…”
Section: Discussionmentioning
confidence: 94%
“…[ 24 ] Popović and colleagues suggested that rs5498 SNP was not significantly correlated with T2DM susceptibility, but its AA genotype was positively associated with annual plaques growth in T2DM patients. [ 25 ] However, a meta-analysis performed by Fan and Liu indicated that rs5498 G allele carriers had lower susceptibility to DR in Asians than those with A allele. [ 26 ] This SNP was also detected in other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…candidate genes of inflammation, oxidative stress, growth factors, renin-angiotensin aldosterone system, and so-forth) has so far been demonstrated in several reports to affect the development of atherosclerosis [2]. Genetic variability in the candidate genes implicated in atherosclerosis may alter their transcriptional activity and contribute to susceptibility to cardiovascular disease [3][4][5][6][7][8][9][10][11]. In the pathogenesis of atherosclerosis genetic, environmental, and epigenetic factors are involved [4][5].…”
Section: Editorialmentioning
confidence: 99%
“…Genetic and epigenetic factors may be studied with two main approaches, candidate gene approach and genome wide association study (GWAS) approach [4][5][6][7][8][9]11]. Candidate gene approach is hypothesis-driven approach, whereas in GWAS approach appropriate subset of patients (i.e.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation